유아 교육기관의 급식 운영실태와 유아의 식사 섭취량 조사 - 이영미(Lee Youngmee); 오유진(Oh Yu-Jin) (Hanʼguk yongyang hakhoe chi, 2005)
Today, the role of kindergarten is more important as nutrition provider through snack and meal services. Desirable kinds and amounts of food items at school lunch menu were important factors of nutrients intakes in children. This study was performed to assess the kindergarten's meal service program (snack and lunch) and the consumption amount of lunch according to each dishes. Twenty four institutions that cared over one hundred children were observed at Seoul and Kyunggido area. Well-trained observers checked meal and snack serving activity and foodservice facilities by formal checklist. And using the weighing method assessed the consumption levels of food items at lunch. During 3 days, 30 children in each kindergarten were selected randomly according to age, observers measured serving and residual weight of each food. The data was compiles by performing ANOVA-test using SPSS WIN 10.0. The result were as follows: 1) Foodservice facilities in kindergarten was limited to provide qualified foodservice. $91.7%$ of institution had kitchen, $41.7%$ had dinning. The kitchen equipment possession rate was $12.5%$ (oven), $30.8%$ (heating cabinet), $58.3%$ (refrigerator). The rate of using document about foodservice was used $83.3%$ (menu list), $41.7%$ (daily foodservice record), $25%$ (standard recipe). $41.7%$ of institution employed licensed dietitian. Only $41.7%$ of subjects preserved meal after daily meal service. 2) Meal serving size was decided by teacher, $54.5%$ at snack and $43%$ at lunch and pre-divided individual portion type was $36.4%$ at snack and $28.6%$ at lunch. The rate of cleaning activity before meal was $72.2%$ at snack, $90.5%$ at lunch. And nutrition or sanitation education activity was more performed at lunch time, for examples brushing teeth activity was $12.5%$ at snack $85.7%$ at lunch. 3) The consumption amounts of plain cooked rice was $112.7{±}26.1{\cal}g$, cooked rice and cereal was $93.06{±}27.97{\cal}g$, curry rice was $208.35{±}64.84{\cal}g$ and the consumption amounts of these main dishes was significantly different by age (p < 0.001). The consumption amounts of soup was very different according to children's preference. The consumption amounts of seaweed soup was $120.18{±}82.13{\cal}g$, wild sesame and bean-paste soup was $40.64{±}23.16{\cal}g$. The consumption range of kimchis was from $6{\cal}g\;to\;13{\cal}g$, jorim (braised food) was from $3{\cal}g\;to\;25{\cal}g$, fried food (include stir fried, deep fat fried, pan fried) was from $14.5{\cal}g\;to\;22{\cal}g$, vegetable dish was from $3{\cal}g\;to\;16{\cal}g$. These consumption amount of each dishes was not reached recommended portion size of nutritionally planning menu by nutritionist.